Free-Breathing Dynamic Contrast-Enhanced MRI for Assessment of Pulmonary Lesions Using Golden-Angle Radial Sparse Parallel Imaging - Chen, Lihua (J Magn Reson Imaging, 2018)
BACKGROUND: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has been shown as a promising technique for assessing lung lesions. However, DCE-MRI often suffers from motion artifacts and insufficient imaging speed. Therefore, highly-accelerated free-breathing DCE-MRI is of clinical interest for lung exams. PURPOSE: To test the performance of rapid free-breathing DCE-MRI for simultaneous qualitative and quantitative assessment of pulmonary lesions using Golden-angle RAdial Sparse Parallel (GRASP) imaging. STUDY TYPE: prospective POPULATION: 26 patients (17 males, mean age=55.1±14.4) with known pulmonary lesions. FIELD STRENGTH /SEQUENCE: 3T MR scanner; a prototype fat-statured, T1-weighted stack-of-stars golden-angle radial sequence for data acquisition and a Cartesian breath-hold volumetric-interpolated examination (BH-VIBE) sequence for comparison. ASSESSMENT: After a dual-mode GRASP reconstruction, one with 3-second temporal resolution (3s-GRASP) and the other one with 15-second temporal resolution (15s-GRASP), all GRASP and BH-VIBE images were pooled together for blind assessment by two experienced radiologists, who independently scored the overall image quality, lesion delineation, overall artifact level and diagnostic confidence of each case. Perfusion analysis was performed for the 3s-GRASP images using a Tofts model to generate the volume transfer coefficient (K(trans)) and interstitial volume (V(e)). STATISTICAL TESTS: Nonparametric paired two-tailed Wilcoxon signed-rank test; Cohen’s kappa; unpaired student t-test. RESULTS: 15s-GRASP achieved comparable image quality with conventional BH-VIBE (P>0.05), except for the higher overall artifact level in the pre-contrast phase (P=0.018). The K(trans) and V(e) in inflammation were higher than those in malignant lesions (K(trans): 0.78±0.52 min(−1) verse 0.37±0.22 min(−1), P=0.020; V(e): 0.36±0.16 verse 0.26±0.1, P=0.177). Meanwhile, the K(trans) and V(e) in malignant lesions were also higher than those in benign lesions (K(trans): 0.37±0.22 min(−1) verse 0.04±0.04 min(−1), P=0.001; V(e): 0.26±0.12 verse 0.10±0.00, P=0.063). CONCLUSION: This feasibility study has demonstrated the performance of high spatiotemporal resolution free-breathing DCE-MRI of the lung using GRASP for qualitative and quantitative assessment of pulmonary lesions.